WELDING TECHNOLOGIES USED IN REPAIRING VEHICLE FRAMES AND THEIR IMPACT ON STRENGTH - Isaboev Tokhirjon Mekhmonovich (Modern American Journals, 2025)
This article analyzes methods of restoring structural elements of a vehicle frame using welding, as well as methods for evaluating the strength of the restored zones. Welding technologies, applied materials, and factors affecting the load-bearing capacity of the structure are examined. The results of experimental studies on changes in strength indicators are also presented.
Keywords: vehicle frame, welding, restoration, strength, structure, mechanical properties.